The Model of Disengagement of Talent with Meta-synthesis Method - Ali Asghar Mobasheri; Ali Nasr Isfahani; Hadi Teimouri (مدیریت دولتی)
Objective The disengagement of talent is a significant consequence of mismanagement, presenting Iranian organizations with numerous challenges. Understanding the causes behind talent disengagement has long been a critical concern for managers and researchers alike. However, a review of the existing literature reveals that the antecedents and consequences of talent disengagement have not been systematically or comprehensively addressed within a specific framework. This gap underscores the need for detailed and structured studies on the subject. Consequently, the current research was undertaken with the aim of identifying and modeling the antecedents and consequences of talent disengagement in organizations. Methods This study is a qualitative research project utilizing the meta-synthesis method. Meta-synthesis is particularly effective for combining scattered findings from previous studies to create new conceptual frameworks. The statistical population for this research consisted of previous studies. After an extensive search and review of available sources, the selection of appropriate materials was conducted by evaluating the titles, abstracts, and content of the identified sources. This selection process ensured that only the most relevant sources were included as samples. Data collection involved a thorough examination of the findings from these selected sources. Thematic analysis was employed to analyze and synthesize the data, ultimately leading to the final results. Results After selecting the appropriate sources, the text of each was meticulously reviewed, and primary codes were extracted. These codes were then analyzed, with duplicates removed and similar codes merged based on meaning and concept. The analysis categorized the antecedents of talent disengagement into two primary dimensions: individual factors and organizational factors. The individual factors were further divided into two components: attitudinal factors (such as lack of self-confidence, job dissatisfaction, unclear vision of the future within the organization, perceived injustice, low self-efficacy, perceived lack of organizational support, perceived lack of organizational identity, and work-life conflict) and behavioral factors (including lack of adaptability, low resilience, lack of emotional intelligence, external engagements, unwillingness to engage in political behavior, and weak communication skills). The organizational factors were categorized into five components: job-related factors (such as lack of autonomy, high work stress, lack of job security, insufficient feedback, mismatch between competencies and duties, and limited growth opportunities), cultural factors (inappropriate work environment, prevalence of bullying, political behaviors, individualism, melting pot mentality, and nepotism), structural factors (high formality, bureaucratic structures, centralized decision-making, and structural differentiation), managerial factors (managerial incompetence, Machiavellian tendencies, resistance to criticism, narcissism, and excessive focus on work), and process-related factors (weak compensation systems, poor communication processes, ineffective performance management, and inadequate talent management and succession planning). Additionally, the consequences of talent disengagement were identified in two dimensions: individual consequences (comprising attitudinal and behavioral components) and organizational consequences (encompassing both short-term and long-term impacts). Conclusion The findings of this research can significantly enhance managers' understanding of the causes behind talent disengagement in organizations. By identifying these antecedents, the study provides a valuable foundation for planning and implementing necessary measures to prevent and manage talent disengagement. Furthermore, recognizing the consequences of disengagement highlights the critical importance of this issue, increasing managerial awareness and sensitivity towards effectively managing this detrimental phenomenon in organizations.